Effect of strain relaxation on performance of InGaN/GaN green LEDs grown on 4-inch sapphire substrate with sputtered AlN nucleation layer - Hu, Hongpo (Sci Rep, 2019)
Here we demonstrate high-brightness InGaN/GaN green light emitting diodes (LEDs) with in-situ low-temperature GaN (LT-GaN) nucleation layer (NL) and ex-situ sputtered AlN NL on 4-inch patterned sapphire substrate. Compared to green LEDs on LT-GaN (19 nm)/sapphire template, green LEDs on sputtered AlN (19 nm)/template has better crystal quality while larger in-plane compressive strain. As a result, the external quantum efficiency (EQE) of green LEDs on sputtered AlN (19 nm)/sapphire template is lower than that of green LEDs on LT-GaN (19 nm)/sapphire template due to strain-induced quantum-confined Stark effect (QCSE). We show that the in-plane compressive strain of green LEDs on sputtered AlN/sapphire templates can be manipulated by changing thickness of the sputtered AlN NL. As the thickness of sputtered AlN NL changes from 19 nm to 40 nm, the green LED on sputtered AlN (33 nm)/sapphire template exhibits the lowest in-plane compressive stress and the highest EQE. At 20 A/cm(2), the EQE of 526 nm green LEDs on sputtered AlN (33 nm)/sapphire template is 36.4%, about 6.1% larger than that of the green LED on LT-GaN (19 nm)/sapphire template. Our experimental data suggest that high-efficiency green LEDs can be realized by growing InGaN/GaN multiple quantum wells (MQWs) on sputtered AlN/sapphire template with reduced in-plane compressive strain and improved crystal quality.